Du positionnement épistémologique aux données de terrain - Françoise Demaizière; Jean-Paul Narcy-Combes (Recherches en didactique des langues et des cultures)
As an introduction to an academic seminar whose theme is research methodology, this paper presents an epistemological reflection on research in the field of second language learning and teaching. Firstly, the oppositions between methodology and method as well as between comprehensive and explanatory approaches to research are discussed, then, the paper stresses the need for the researcher to make his epistemological position explicit and underlines the fact that this position cannot but depend on the researcher’s social environment and the interplay of influence that this fosters. Language learning and teaching research belongs to the larger field of the social sciences and the question of distanciation and objectivity is analysed. The use of various complementary approaches to research is advocated in order to go beyond certain continua (such as the nomothetic - idiographic continuum and the opposition of qualitative and quantitative approaches). In order to be able to construct his theoretical framework and to adopt the most appropriate methodology, the researcher needs to clarify the way he sees the various scientific domains he refers to, triangulation and research validity. The link between the context and the data in various research methodologies will then be discussed. The specific background of each researcher's history plays an important part, but the coherence of the researcher’s choices, the solidity of his epistemological position and his openness to debate are what make scientific debates possible. These debates play a constituent role in the construction of scientific knowledge.